Modification of isolation methods and physico-biochemical properties of preparations of fungal oxidoreductases - O. V. Fedotov; Z. L. Usikova (Regulatory Mechanisms in Biosystems, 2020)
The results of the modification of methods for producing enzymatic preparations (EP) of peroxidases and catalases of extra- and intracellular finding from fungal cultures are presented. Strains of Flammulina velutipes F-vv, Lentinula edodes 523 and Pleurotus ostreatus P-01 were used as producers of oxidoreductases. The producers were cultured in glucose-peptone medium, modified for each strain. Protein fractionation was carried out by leaching with ammonium sulfate at a saturation of 40–70% for peroxidases and 80% for catalases. The obtained solutions of protein fractions were additionally subjected to purification by dialysis, gel filtration on Molselect G-50 and G-75 granules, and also freeze drying. The yield of enzymatic preparations per unit mass of mycelium and the volume of culture fluid were calculated. The individual characteristics of EP – enzymatic activity, the mass percentage of protein and associated amino acids, the ratio of the latter in groups depending on the nature of the radicals (amphotericity) of protein molecules are established. It was proved that the amino acid content in the proteins of fungal EP catalases and peroxidases indicates their acidic nature and this is confirmed by the pH values of aqueous solutions. Examination and toxicity testing of enzymatic preparations were carried out in certified laboratories, which confirmed their characteristics and compliance with safety requirements. The therapeutic properties of amino acids that are part of proteins or are in a free state in enzyme preparations are analyzed. In this way, the methods have been developed for producing enzymatic preparations of peroxidases and catalases of extra- and intracellular location, which allow new antioxidant enzymes with individual properties to be obtained, and, as a result, bring prospects for use in various industries and scientific research.